Nostalgic Senses - Zantides, Evripides (My University, 2012)
Santorini Biennale mission is to promote both emerging and established artists that are working on the borders between different art disciples, allowing them to surpass the traditional (and perhaps limiting) concepts of classicism, modernism, contemporary and applied arts. The Santorini Biennale will be dedicated to hosting artist-led events presented in full co-operation with the organizers. The Santorini Biennale is inspired by the ways in which ideas are born and disseminated – how they then develop and diversify within our increasingly interconnected global society. Art and culture continue to play a distinctive role in defining and re-examining the past, understand the present and imagine the future direction of human endeavour. In recognition of this, the Santorini Biennale wishes to cultivate a spirit of research and experimentation; also, to present an environment ideal for open and continuous dialogue. Pursuing a programme of cultural collaboration that is at the same time both regional and international, Santorini Biennale intends to support and promote the free exchange of both artistic and cultural experience. Reflecting the strengths of co-operation across all borders, encouraging and rewarding excellence, Santorini Biennale will work to advance a broad framework of activities enabling participants to initiate a wider dialogue for new ideas and social change. Ideally, by our art, we can provoke and motivate humanity to take action on today’s fundamental issues.
Keywords: Art Installation; Ceramic Art Drawing; Collage Art; Comic Art